1994
DOI: 10.1203/00006450-199407001-00016
|View full text |Cite
|
Sign up to set email alerts
|

Collection and 28-Day Storage of Human Placental Blood

Abstract: Placental blood was harvested using a novel collection system into packs containing citrate-phosphate-dextroseadenine and then stored for 28 d. Before and during storage, sterility, adequacy of anticoagulation, blood chemistry, and red cell viability were assessed weekly. The average volume of blood collected was 65 mL (range 30-110 mL) with a 0.42 hemocrit once diluted in anticoagulant. All blood culture specimens were sterile at collection and during storage. In the United States, more than 40 000 VLBW infan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
42
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 29 publications
4
42
1
Order By: Relevance
“…Various studies have reported microbial contamination rates of between 0 and 9% [17,18,20,23,32]. More recent examination methods have revealed that iatrogenic bacterial contamination during blood removal deserves less attention than contamination caused by bacteraemia already existing in the newborn due to an amnion infection syndrome [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Various studies have reported microbial contamination rates of between 0 and 9% [17,18,20,23,32]. More recent examination methods have revealed that iatrogenic bacterial contamination during blood removal deserves less attention than contamination caused by bacteraemia already existing in the newborn due to an amnion infection syndrome [31,32].…”
Section: Discussionmentioning
confidence: 99%
“…Autologous blood transfusions have been shown to be safe in both adult and pediatric patients (17,21,25). Umbilical/placental cord blood is autologous blood from a neonate (20), and the use of autologous umbilical cord blood (UCB) has long been discussed among neonatologists (5,6,9,10,29). Owing to the increasing utilization of UCB for the transplantation of hematopoietic stem cells, significant progress has been made in developing safer and more efficient collection techniques for UCB (12,14).…”
mentioning
confidence: 99%
“…Even at cesarean section, intraoperative autologous blood collection and transfusion has shown to be a safe procedure [69]. Umbilical cord blood obtained at delivery after cord clamping has been suggested as a source of autologous blood for transfusion in neonates [70]. In preterm newborns, but also in term newborns with serious congenital conditions which have to be surgically corrected soon after birth (e.g.…”
Section: Use Of Cord Blood For Autologous Transfusionmentioning
confidence: 99%
“…Later, interest came up to collect and store cord blood for later autologous use [74]. Because concern arised [75] from studies with open syringetype collection systems revealing significant bacterial contamination in stored cord blood samples [76], recent studies used closed systems to collect cord blood into anticoagulantcontaining bags [70]; some autologous cord blood samples have been transfused in preterm neonates [77][78][79]. We ourselves performed a prospective study to determine the feasibility of cord blood collection for autologous transfusion in preterm neonates [80].…”
Section: Use Of Cord Blood For Autologous Transfusionmentioning
confidence: 99%